An electrochemical investigation of platinum group minerals - Tadie, Margreth (Centre for Minerals Research, 2015)
The Bushveld complex is the largest ore body in the world hosting platinum group elements (PGEs). It is a stratified orebody with three major reefs namely, the Merensky reef, UG2 reef and the Platreef. Platinum and palladium are the most abundant PGEs found in the Bushveld complex. They occur in the form of minerals/mineral phases with elements such as sulphur, tellurium, arsenic and iron. These minerals/mineral phases are associated with base metal sulphides occuring along grain boundaries. Unlike the Merensky and UG2 reef, the Platreef is almost barren of PGE sulphides and the distribution of base metals sulphides and their association with PGMs is erratic. Froth flotation targeted at the recovery of base metal sulphides is implemented in PGM concentrators to concentrate PGMs. Flotation of sulphide minerals is achieved with the use of thiol collectors to create hydrophobicity, and copper sulphate is often used to improve hydrophobicity and therefore recovery. Sodium ethyl xanthate (SEX) and sodium diethyl dithiophosphate (DTP) are commonly used as collectors on PGM concentrators. The erratic mineral variations in the Platreef ore, however, raise the question of the effectiveness of the application of sulphide mineral flotation techniques on this ore. Previous work by Shackleton, (2007) investigated the flotation of PGE tellurides, sulphides and arsenides. The study highlighted that the mechanisms with which these minerals interact with collectors and with copper sulphate was poorly understood. It is as a result of the findings of Shackleton's work that this study aims to elucidate the fundamental interactions of telluride and sulphide PGMs with thiol collectors and with copper sulphate. Subsequently this work also aims to compare the behaviour of these reagents on sulphide PGMs and telluride PGMs.